'Except in the case of historical fact': history and the historical novel. Issue 1 (2nd January 2016) - Wake, Paul
Abstract : The relationship between history and fiction has long been recognised as close but problematic and there are few places in which the problematics of this relationship manifest more clearly than in the case of the historical novel. Concerned with the borderland space in which history meets fiction, this reading of the historical novel is accompanied by the reading of another borderline case, that of popular narrative history, in the expectation that the proximity of these two modes of writing will allow insight into the workings of both. Drawing on Gérard Genette's Paratexts (1997), my interpretation of the relation between history and historical fiction turns on notions of hospitality, connecting Genette's work with that of Jacques Derrida in order to outline a model of generic intersection in which historical fiction appears as the malign guest of historiography, for whom the hospitality of historical writing necessarily entails hostility at the threshold. More precisely, I will argue that it is this hostility (hostipitality) that guarantees the integrity of the threshold dividing history and fiction while at the same time calling into question the assumptions underlying the status of fiction as guest and history as host.